1991
DOI: 10.1128/iai.59.12.4599-4605.1991
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease-sensitive binding of an Actinobacillus actinomycetemcomitans leukotoxin to the bacterial cell surface

Abstract: A leukotoxin of Actinobacilus actinomycetemcomitans 301-b was solubilized from cell-associated membrane vesicles by treatment with externally added DNase and RNase and was further purified by a procedure which included ammonium sulfate fractionation, gel filtration chromatography, and ion-exchange chromatography. The purified toxin had a molecular mass of 113,000 Da by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and a high isoelectric point (approximately 8.8). From these characteristics, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…Considering the present results and those previously reported (21)(22)(23)(24), the following possibilities are suggested for the association of leukotoxin to A. actinomycetemcomitans. Leukotoxin is bound to bacterial and vesicle surfaces by weak interactions mediated by electrostatic forces or by hydrophobic protein epitopes, this amount of toxin being removed with 0.3 m NaCl, serum ( £ 20%), or low (< 1 m) urea concentrations.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Considering the present results and those previously reported (21)(22)(23)(24), the following possibilities are suggested for the association of leukotoxin to A. actinomycetemcomitans. Leukotoxin is bound to bacterial and vesicle surfaces by weak interactions mediated by electrostatic forces or by hydrophobic protein epitopes, this amount of toxin being removed with 0.3 m NaCl, serum ( £ 20%), or low (< 1 m) urea concentrations.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to its membrane-destabilizing action, NaCl also displaces electrostatic interactions that could mediate binding of leukotoxin to charged molecules, such as LPS and nucleic acids. The latter association mechanism was suggested by Ohta et al (21,22) who showed release of the toxin from the bacteria upon treatment with nucleases. However, the portion of leukotoxin released by this treatment is less than that removed by NaCl (data not shown).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, any toxic eect against PMNL requires contact of the bacteria with the cell membrane of PMNL. Though certain conditions such as presence of nucleases and increased ionic strength of the surrounding medium cause leukotoxin release from the bacteria (21,34), it is possible that in vivo the bacteria keep the leukotoxin bound to the cell surface. Carriage of leukotoxin on its surface could thus confer a particular advantage to A. actinomycetemcomitans upon challenge with PMNL.…”
Section: Discussionmentioning
confidence: 99%
“…When the anaerobic fructose-limited chemostat culture was in a steady state, the amount of cell surface DNA was estimated to be about 20% of the total cellular DNA (26). The mechanism for the extracellular localization of DNA is unknown, but bacterial autolysis does not seem to be involved in the process (28).…”
mentioning
confidence: 99%